Auto bibliographical research: Emergency Remote Education in times of pandemic - Natálya da Conceição Sobrinho Gato (Universidade Federal do Oeste da Bahia, 2021)
The development of this article combined with my willingness to record the events related to education in times of pandemic, providing a better understanding of the facts arising from that period through an autobiographical narrative. According to Passeggi (2016), autobiographical narratives, applied as a research method, provide the subject with the ability to present and reflect on their own history. This short introduction will not end the discussion about Emergency Remote Education, as there are several arguments to be said related to the subject and the pandemic has not yet ended. Therefore, this article aims to report and analyze Remote Emergency Education based on the auto bibliographical research implemented in the state of Minas Gerais through Federal Law No. 13,979, of February 6, 2020, which provides for measures to facing the public health emergency of international importance due the coronavirus outbreak of 2019 (Brazil, 2019).